The analysis of energy consumption and greenhouse gas emissions of a large-scale commercial building in Shanghai, China. (26th February 2016) - Wang, Xin; Huang, Chen; Zou, Zhijun
Reasonable test, diagnosis, and analysis are meaningful for building energy efficiency retrofit and management. Energy consumption and greenhouse gas emission of a large-scale commercial building are described in this article. Basic information about energy consumption equipment is included in the investigation. Further diagnoses about the operational state of air-conditioning water systems, and ducted systems were implemented. Energy consumption decreased 200 kWh/m 2 per year from 2007 to 2009 after energy-saving reconstruction in 2006. Next, a carbon audit was carried out; this comprised CO2 emission statistics associated with the energy use and categorization and structural analysis (categorization refers to energy categorization and structural analysis means the composition and its proportion relationship of all kinds of primary energy and secondary energy in energy production or consumption). Greenhouse gas emissions could be less than 150 kg/m 2 per year from 2007 to 2009. An analysis of the correlation between CO2 emissions, building gross domestic product, and energy efficiency is also presented. This article makes an analysis on the energy utilization and energy-saving reconstruction of a public commercial building in Shanghai and then makes an analysis of carbon audit about greenhouse gas emissions related to energy utilization (it analyzes the status of building's energy utilization and greenhouse gas emissions), to have a more comprehensive understanding on the internal relationship between energy consumption and its greenhouse gas emissions and provide researchful reference data for the development with reduction strategies of greenhouse gas emission in future building.